Short- and long-chain perfluorinated acids in sewage sludge from Shanghai, China - Yan, Hong; Zhang, Chao-Jie; Zhou, Qi; Chen, Ling; Meng, Xiang-Zhou (Chemosphere (Oxford), 2012)
► We determined C3–C14 PFAs in sewage sludge from 25WWTPs in Shanghai, China. ► PFAs pollutants were ubiquitous in sludge with the ∑PFAs range of 126–809ngg−1. ► Unlike previous studies, PFOA was dominant and much higher than those reported. ► Concentrations of short-chain PFAs (<C6) in sewage sludge were considerable. ► Rather than indirect source, sorption from sewage is main source of PFAs in sludge. Perfluorinated acids (PFAs) are the subject of increasingly intense environmental research. In this study, sewage sludge samples were collected from 25 wastewater treatment plants (WWTPs) in Shanghai, China to evaluate the levels and profile of C3–C14 PFAs. The results showed a ubiquitous PFAs contamination of sewage sludge in Shanghai with the total PFAs (∑PFAs) range of 126–809ngg−1dw. Perfluorooctanoic acid (PFOA) was found to be the dominant PFA pollutant and its concentration ranged from 23.2 to 298ngg−1dw, much higher than the levels in other countries. Moreover, concentrations of short-chain PFAs (<C6) in sewage sludge were considerable. Following sludge application in agricultural land, the concentrations of PFOA, and perfluorooctane sulfonate (PFOS) are predicted to be 1.08 and 7.53ngg−1dw, respectively, much lower than the corresponding US EPA standards. Nevertheless, further studies are needed to explore the fate of PFAs in sludge-amended soils due to the persistence and bioaccumulation potential of these compounds.